ANALISIS KESALAHAN MORFO-SINTAKSIS PADA KARANGAN EKSPOSISI BAGI SISWA KELAS XI SMA NEGERI 11 MAROS - Sumarni, Sumarni; Darwis, Muhammad; Lewa, Inriati (JURNAL ILMU BUDAYA, 2019)
This study aims to explain the forms of errors that include the use of syntactic construction errors in the exposition essay of 11th grade students of Maros 11 Senior High School The method used in this study is a method of reading with note-taking techniques. The source of this research data is an exposition essay of the eleventh grade students of SMA 11 Maros in the academic year of 2017/2018.The research method used is perspective method, which describes a natural state of misuse of syntactic construction in the exposition essay of 11th grade students of 11 Public High Schools. The results showed that the syntactic construction error in the exposition essay in class XI of SMA 11 Maros was in the form of two types of errors, namely the first in the form of error phrases including diction, prepositions, phrase structure, excessive elements, superlative overload, and reciprocal forms. Furthermore, the second mistake in the form of sentence errors is three, namely the error of the subject that is not subject, the error of the sentence that is not predicated, and the mistake of conjunction. The phrase and sentence errors are errors that occur due to omission, addition, misformation, missordering.